Dental Caries Rate for Permanent First Molars among Children Aged 8-9 Years - Cahyani, Putri Indah; Ningsih, Neny Setiawaty; Fathiah, Fathiah; Herlina, Rita (Dental Therapist Journal, 2023)
Caries in permanent first molars is the main cause of the high prevalence of extractions since the first molars are the first teeth to erupt. Such eruption is due to poor behavior in maintaining dental health as well as the anatomical shape of the first molars which have pits and fissures as the places for the food waste to stop. This study aims to determine the dental caries status of permanent first molars among children aged 8-9 years at SDN 35 of North Pontianak. This was a descriptive study with a survey method. The results of the study showed that the highest caries incidence rate of 20% was found in the first permanent molars, namely tooth 4.6. Caries incident was mostly found among female respondents by 69% and aged 9 years by 64%. It can be concluded that there were 65 healthy teeth with the highest number for tooth 1.6 by 48%. Furthermore, there were 119 dental caries with the highest number for tooth 4.6 by 78%. The rates of dental caries among female respondents and those aged 9 years were higher by 69% and 64%, respectively. Dental caries rate among respondents aged 9 years were larger, namely 64%. It is recommended to conduct further study regarding the level of understanding in maintaining dental health among children.